A Short‐Term Western Diet Impairs Cholesterol Homeostasis and Key Players of Beta Amyloid Metabolism in Brain of Middle Aged Rats. Issue 16 (20th July 2020) - Spagnuolo, Maria Stefania; Pallottini, Valentina; Mazzoli, Arianna; Iannotta, Lucia; Tonini, Claudia; Morone, Barbara; Ståhlman, Marcus; Crescenzo, Raffaella; Strazzullo, Maria; Iossa, Susanna; Cigliano, Luisa
Abstract : Scope: Cholesterol homeostasis is crucial for brain functioning. Unhealthy nutrition can influence cerebral physiology, but the effect of western diets on brain cholesterol homeostasis, particularly at middle age, is unknown. Given the link between brain cholesterol alteration and beta amyloid production, the aim is to evaluate whether a diet rich in fat and fructose affects the protein network implicated in cholesterol synthesis and shuttling between glial cells and neurons, as well as crucial markers of beta amyloid metabolism. Methods and results: Middle aged rats are fed a high fat–high fructose (HFF) or a control diet for 4 weeks. Inflammatory markers and cholesterol levels significantly increase in hippocampus of HFF rats. A higher activation of 3‐hydroxy 3‐methylglutaryl coenzyme‐A reductase, coupled with lower levels of apolipoprotein E, LXR‐beta, and lipoproteins receptors is measured in hippocampus from HFF rats. The alteration of critical players of cholesterol homeostasis is associated with increased level of amyloid precursor protein, presenilin 1, and nicastrin, and decreased level of insulin degrading enzyme. Conclusions: Overall these data show that a western diet is associated with perturbation of cholesterol homeostasis in middle aged rats, mostly in hippocampus. This might trigger molecular events involved in the onset of neurodegenerative diseases. Abstract : This study evaluates whether a western diet, rich in fat and fructose, can affect, during middle age, crucial players implicated in brain cholesterol and beta amyloid homeostasis. The western diet is associated with perturbation of cholesterol homeostasis in middle aged rats, mostly in hippocampus, and this alteration is associated to molecular events that can trigger the onset of Alzheimer's disease.